A 10–40 GHz switched step attenuator in 0.13 µm CMOS technology. Issue 2 (3rd April 2017) - Askari, M.; Kaabi, H.; Kavian, Y. S.
ABSTRACT: A 4-bit switched step attenuator is designed and presented at 10–40 GHz. Body-switching technique is used to improve attenuation range and flatness of the proposed attenuator. The circuit is implemented in a standard 0.13 µm CMOS technology and the simulation results are reported. The design shows approximately constant attenuation range of 13.5 dB across the frequency band. The flatness is less than 1.5 dB in the reference state and less than 1.8 dB in the attenuation state. Moreover, the input and output return losses are better than 12 dB and the minimum IIP3 is greater than 23.5 dBm across the operating frequency.